55.2k views
4 votes
Can you help me thank you

Can you help me thank you-example-1

1 Answer

5 votes

Answer:

A.)
(1)/(5^6)

Explanation:

To simplify
(5^2)^3, use the exponent rule that states
(a^m)^n=a^(mn)

So,


(5^2)^3=5^(2*3)=5^6

Use the same exponent rule to begin simplifying
(5^4)^(-3):


(5^4)^(-3)=5^(4*(-3))=5^(-12)

To further simplify
5^(-12), use the exponent rule that states
a^(-m)=(1)/(a^m)

So,


5^(-12)=(1)/(5^(12))

Then multiply the two new expressions as indicated in the original problem:


(5^6)((1)/(5^(12)))=(5^6)/(5^12)=(1)/(5^6)

Alternatively, you could use the exponent rule that states
a^m*a^n=a^(m+n)

where


a^m=5^6\\a^n=5^(-12)

So,


(5^6)(5^(-12))=5^(6+(-12))=5^(-6)=(1)/(5^6)

User Mark Holland
by
4.5k points